To have and have not [videorecording (DVD)] - Hawks, Howard, 1896-1977; Hawks, Howard, 1896-1977; Bogart, Humphrey, 1899-1957; Brennan, Walter, 1894-1974; Bacall, Lauren, 1924-2014; Hemingway, Ernest, 1899-1961 (Warner Home Video, 2005)
An American charter boat captain in Martinique gets involved with a young female drifter and some French freedom fighters who are trying to elude local Nazi collaborators.